Students' perception of energy poverty—A comparative analysis between local and exchange university students from Montevideo, Lisbon, and Padua - Castro, Carolina Cruz; Gouveia, João Pedro (Frontiers in Sustainable Cities, 2023)
Energy Poverty (EP) is a growing concern in EU and national policies. Limited research has been conducted on students' perception of EP and vulnerability to EP, especially on how this may be modified if the student is a local or an exchange university student and how this interacts with the season (i.e., summer, winter). Therefore, the present research aims to deepen this understanding by analyzing and comparing students' perceptions of EP and exploring their vulnerability to EP, considering their background and the city they live in, using Montevideo in Uruguay, Lisbon in Portugal, and Padua in Italy, as case studies. To achieve these aims, two populations of university students in each city were surveyed: one of Local Students (LS) and another of Exchange Students (ES). Responses from 295 students to an online survey with forty-four questions covering several aspects of EP and energy awareness, such as energy consumption habits, vulnerability drivers, energy equipment, and lived experience in maintaining comfortable internal temperatures, were collected in 2022. Differences between the perception of LS and ES in each city were analyzed, as well as differences in students' perceptions among cities. Although it is difficult to generalize, comfort levels seem to vary according to location, type of students, and season, but according to the results, there seems to be an interaction between these three factors. According to this research, most students did not identify themselves as living in EP, but several populations perceived discomfort in both winter and summer, showing their vulnerability to EP.